Results and Applications in Statistical Queuing Theory - Ferreira, M. A. M. (EasyChair Preprint Nº 7902, 2025)
A theory of queues overview, single node and in network is presented. Some important results are highlighted. And practical applications, the must of them uncommon but some very well known, using mainly infinite servers nodes are outlined.